Non-Invasive Heat-Induced Numerous Tissue Ablation Using High Intensity Focused Ultrasound Technique - Naziba, Anika Tun; Uddin, Mohammad Nasir (AIUB Journal of Science and Engineering (AJSE), 2022)
In biomedical sector, High Intensity Focused Ultrasound (HIFU) is a non-invasive treatment that employs quasi acoustic waves to raise the temperature. According to its high efficiency and cheap cost, it has been the main focus of this research. The key stages of this tumor ablation include mechanical and thermal effects. Multiple tissue ablations were analyzed using HIFU simulation to optimize intensity, power, focal length, and lens radius of curvature to maximize tumor ablation while minimizing collateral harm to healthy tissue in the surrounding area. This model analysis incorporates clinical applications in order to determine the most optimum parameters. To accomplish this study, numerous types of human soft and hard tissue were considered. At a specific acoustic power and exposure time, the optimal frequency (1.6 MHz to 3.5 MHz) and power (120 W to 140 W) for each tissue were determined for effective tissue ablation. This study conducted all calculations by changing the lens focal length from 55 mm to 65 mm. The results of this procedure usually require a few weeks to safely and efficiently remove the tumor. Due to this optimum outcome, it indicates that the HIFU tumor ablation procedure has a high probability of success in the medical sector.